2019
DOI: 10.26452/ijrps.v10i2.782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute Atorvastatin treatment in an experimental model of colitis

Abstract: Acute atorvastatin treatment in an experimental model of colitis was studied using the acetic acid induction modality for colitis in rats. This study was aimed to evaluate possible therapeutic effects of atorvastatin against acetic acid-induced colitis in a rat model and to find out the correlation between severity index with oxidative stress parameters and inflammatory markers. Experimental colitis was induced in rats by rectal administration of 4% acetic acid (vol/vol). Rats with colitis were received either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Treatment with 10 mg/kg ATV in this study reduced the scores and delayed the onset of diarrhea. Similarly, other studies using rosuvastatin, simvastatin, and ATV in colitis models have demonstrated a reduction in the disease activity index (22,46,47).…”
Section: Discussionmentioning
confidence: 61%
“…Treatment with 10 mg/kg ATV in this study reduced the scores and delayed the onset of diarrhea. Similarly, other studies using rosuvastatin, simvastatin, and ATV in colitis models have demonstrated a reduction in the disease activity index (22,46,47).…”
Section: Discussionmentioning
confidence: 61%
“…In addition, statins have been highlighted in reducing lipid peroxidation. This effect was also observed in the studies analyzed, 25,27,30,35,36,39,40 which described the reduction in Malondialdehyde (MDA) and 2‐thiobarbituric acid (TBA) In experimental UC, MDA is generally increased Oxygen radicals produce membrane peroxidation and MDA formation, which are detrimental to cell function 100–102 . However, statins have stood out in reducing MDA 99,103 …”
Section: Discussionmentioning
confidence: 68%
“…They are quickly mobilized to the infection sites and exert their defenses against microorganisms through phagocytosis and the release of soluble and protein antimicrobial compounds 76 . Usually, high levels of MPO are found in IBD, and among the studies analyzed, all detected an increase in the levels of this enzyme in animals with UC 25,27,35,40,41,77 . Statins have been reported to reduce mRNA levels of the MPO gene by 20‐ to 200‐fold in monocyte–macrophage and bone marrow precursors 78 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation